Hall and ion slip effects on MHD rotating boundary layer flow of nanofluid past an infinite vertical plate embedded in a porous medium - M. Veera Krishna; Ali J. Chamkha (Results in Physics, 2019)
The diffusion-thermo, radiation-absorption and Hall and ion slip effects on MHD free convective rotating flow of nano-fluids (Ag and TiO2) past a semi-infinite permeable moving plate with constant heat source are discussed. Making use of Perturbation technique, we found velocity, temperature and concentration and are discussed through graphs. We evaluated the skin friction, Nusselt number and Sherwood number analytically and computationally discussed. The resultant velocity reduces with increasing rotation parameter and enhances with increasing Hall and ion slip parameters and Dufour parameter. Radiation-absorption parameter leads to increase the thermal boundary layer thickness. Nusselt number decreases with suction parameter and Sherwood number increases chemical reaction parameter. Keywords: Dufour effect, MHD, Hall and ion slip effects, Nanofluid, Radiation-absorption